Toxicity Determination of Some Insecticides Against Trichogramma chilonis Ishii - Khulbe, Pooja; Kumar, Arvind (Indian Forester, 2015)
The screening of some insecticides viz. monocrotophos, chlorpyriphos, cypermethrin and imidacloprid was done to determine the LC50 values against Trichogramma chilonis. Imidacloprid was found most toxic to Trichogramma chilonis, at thirty minute, one, two and six hour after treatment with their lowest LC50 value of 0.07, 0.03, 0.075, and 0.00004 per cent respectively followed by cypermethrin. While, chlorpyriphos and monocrotophos was found least toxic to the T. chilonis with its higher LC50 value. Thus, the monocrotophos and chlorpyriphos can be safely used in field application with T. chilonis in I.P.M. programme. While, imidacloprid should be avoided or used in alternatively with T. chilonis under strict supervision in field application.